Studi Deskriptif Proses Berkarya Seni Mozaik Berbahan Biji-Bijian Pada Kelas IV SD Negeri 54 Bengkulu Selatan - Yeta, Yeta; Parmadie, Bambang (JURIDIKDAS, 2025)
This study aims to describe the process of making and producing grain-based mosaic art in class IV primary school number  54 Shout Bengkulu. This type of research uses a qualitative descriptive research type. The research subjects in this study were fourth grade students at primary school number 54 of South Bengkulu. The instrument in this study was the researcher himself using observation guidelines, interview guidelines and documentation. Data analysis through data collection, data reduction, data presentation, and drawing conclusions. Data collection techniques in the form of observation, interviews, and documentation studies. Data validity techniques through triangulation and member checks. The results of this study are (1) the process of making mosaic works made from grains by preparing tools and materials such as pencils, erasers, rulers, glue sticks, scissors, and markers, while the materials are corn kernels, mung bean seeds, Chinese petai seeds, glutinous rice seeds, fox glue and A3 drawing paper. Prepare motif designs, prepare motif designs, namely floral, butterfly and rabbit motifs. The technique of attaching it is by gluing the grain material on the base of the motif design that has been smeared with fox glue. Finally, by checking the work again, if there is a motif design that has not been covered, the students cover it with grain material and do the drying process in the sun with the aim that the glue dries quickly and the grain material does not come off easily. (2) works made of grain that have been made by students by paying attention to the elements of line, plane, color, texture, and darkness as well as the principles of unity, balance, rhythm, emphasis, proportion, and harmony. The conclusion in this study is that the manufacturing process consists of 4 steps, namely preparing tools and materials, preparing motif designs, pasting techniques and final finishing, while the results of his work are mosaics of flowers, butterflies and rabbits.